2018
DOI: 10.1002/2017jd027194
|View full text |Cite
|
Sign up to set email alerts
|

CAUSES: On the Role of Surface Energy Budget Errors to the Warm Surface Air Temperature Error Over the Central United States

Abstract: Many weather forecast and climate models simulate warm surface air temperature (T2m) biases over midlatitude continents during the summertime, especially over the Great Plains. We present here one of a series of papers from a multimodel intercomparison project (CAUSES: Cloud Above the United States and Errors at the Surface), which aims to evaluate the role of cloud, radiation, and precipitation biases in contributing to the T2m bias using a short‐term hindcast approach during the spring and summer of 2011. Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 44 publications
0
97
1
Order By: Relevance
“…The surface energy budget analysis shows that both surface solar radiation and evaporative fraction errors are contributors to the warm bias. These findings based on long‐term climate simulations are similar to those discovered from short‐term hindcast experiments (Ma et al, ; Van Weverberg et al, ), although short‐term hindcasts in general have smaller warm bias which is associated with smaller errors in radiation and evaporative fraction compared to climate simulations. The relative magnitude of biases between hindcast and climate simulations is consistent with an interaction between large‐scale circulation and physical processes that amplifies the warm bias at the surface in climate integrations.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The surface energy budget analysis shows that both surface solar radiation and evaporative fraction errors are contributors to the warm bias. These findings based on long‐term climate simulations are similar to those discovered from short‐term hindcast experiments (Ma et al, ; Van Weverberg et al, ), although short‐term hindcasts in general have smaller warm bias which is associated with smaller errors in radiation and evaporative fraction compared to climate simulations. The relative magnitude of biases between hindcast and climate simulations is consistent with an interaction between large‐scale circulation and physical processes that amplifies the warm bias at the surface in climate integrations.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…EAM temperatures are much warmer over the NH continents in winter poleward of 40°N due at least in part to the tuning choices used in the Bergeron process, although the amplitude of the temperature bias is about the same magnitude. Temperature biases in the same regions in NH summer are much reduced compared to CAM5 and many other climate models (Ma, Klein et al, 2018). EAM is also generally warmer over sea ice and ice sheets, particularly in winter, and this is due to the substantial changes in the surface energy budget due to differences in clouds and the surface energy budget discussed below.…”
Section: 1029/2019ms001629mentioning
confidence: 92%
“…Since brute force strategies using many multiyear simulations were not feasible at high resolution, other strategies were employed. Xie et al () and H. Ma, Klein, et al () showed that model biases related to fast physical processes in short‐term hindcasts resemble those from long‐term climate simulations, so two frameworks using short simulations were used as an integral part of model development. A hindcasting methodology identified with Transpose‐AMIP (Atmospheric Model Intercomparison Project) and Cloud‐Associated Parameterizations Testbed (Phillips et al, ; Williams et al, ) was used to assess candidate physical parameterizations and tune the computationally expensive high‐resolution EAM configurations, following protocols described in previous studies (Boyle & Klein, ; Liu et al, ; Lin et al, ; Qian et al, ; H. Ma, Klein, et al, ; van Weverberg et al, ; Xie et al, ).…”
Section: Model Configurations Tuning and Computational Performancementioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that whatever combination of physical processes it is that is leading to the diurnal cycle of the T2M error having the shape and phase that it does at SGP, that behavior is likely to also be happening over a much wider area in many of the models. As a result, detailed evaluations of cloud-and-radiation and land surface issues at SGP, such as those presented by Van Weverberg et al (2018) and Ma et al (2018), respectively, have the potential to lead to significant reductions in the magnitude and extent of the warm biases which have been presented here.…”
Section: 1002/2017jd027199mentioning
confidence: 98%